Practical Skills in Early Childhood Education for Sustainable Vocational Readiness: A Systematic Literature Review - Sholihah, Abdah Munfaridatus; Subaidi, Ju'; Basuki, Basuki (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to analyze trends, themes, contributions, and gaps of previous research on early childhood practical skills as the foundation of sustainable vocational readiness in the perspective of the Sustainable Development Goals (SDGs). This study uses the Systematic Literature Review design with PRISMA stages, namely identification, screening, eligibility, and included. Data were obtained through Publish or Perish from Google Scholar and CrossRef with a publication range of 2020–2025. From the initial 300 articles, screening was carried out based on titles, abstracts, keywords, topic suitability, and availability of bibliographic information, so that 25 priority articles were obtained for analysis. Data was analyzed using thematic synthesis by grouping articles into the themes of practical skills and life skills, SDGs and continuing education, future or vocational readiness, and teacher and curriculum competencies. The results of the study show that practical skills such as self-care, tidying up the learning environment, completing simple tasks, sorting waste, gardening, and working together contribute to the formation of independence, discipline, responsibility, problem-solving, and sustainability awareness. This study concludes that early childhood vocational readiness is not interpreted as direct work readiness, but rather as the initial process of forming productive habits, independent character, and social responsibility relevant to sustainable development.